Optimasi Konsentrasi BHT untuk Menjaga Stabilitas Pigmen Alami pada Sediaan Cream Blush Ekstrak Hemigraphis colorata - Ratih, Hestiary; Sutarna, Titta Hartyana; Al-Hakim, Nur Achsan; Dwijayanti, Anisa (Journal of Pharmaceutical and Sciences, 2025)
The use of natural dyes from Hemigraphis colorata Hall. extract as cosmetic dyes faces stability challenges due to oxidative degradation. This study aims to test the effect of Butylated Hydroxytoluene (BHT) antioxidant concentration on the physical stability and color of cream blush formulations. H. colorata leaves were extracted by maceration and lyophilization, then formulated into four cream blush preparations with varying concentrations of BHT: without BHT (F0), 0.0075% (F1), 0.05% (F2), and 0.1% (F3). Physical stability of the formulations was evaluated for 28 days through organoleptic testing, homogeneity, pH, viscosity, spreadability, adhesion, and color stability using UV-Visible spectrophotometry. The results showed that all formulations met the physical standards for topical preparations. However, F2 (0.05%) and F3 (0.1%) successfully maintained color stability with minimal shifts. This study concludes that BHT can effectively maintain the physical stability of cream blush formulations based on H. colorata extract, with 0.05% (F2) being the optimal BHT concentration (the lowest effective concentration), based on considerations of effectiveness, safety, and cost, proven to be optimal in protecting natural pigments from degradation. These results provide important information for the development of safe, high-quality natural cosmetic products with a longer shelf life.